ANALISIS PEMBENTUKAN KARAKTER KHALIFAH FIL ARDH PADA ANAK USIA DINI MELALUI PROGRAM LITERASI HIJAU (ECO-EDUCATION) - Romenah (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the character formation of the Caliphate (Khalifah fil Ardh) in early childhood through the Green Literacy (Eco-Education) program at Al-Alif Kindergarten in Tokke Village, North Luwu. The character of the Caliphate (Khalifah fil Ardh) is an important foundation in Islamic Religious Education, emphasizing human responsibility as stewards of nature. This study used a qualitative approach with a case study method. Data collection techniques included participatory observation, in-depth interviews with the principal and teachers, and documentation in the form of child development portfolios. The results showed that character formation was achieved through the integration of the Islamic Religious Education (PAI) curriculum with concrete object-based play activities, such as gardening and waste management. Assessment procedures were conducted periodically and comprehensively using anecdotal notes and a developmental checklist. Furthermore, the principal's academic supervision played a crucial role in guiding teachers in developing innovative, technology-based learning strategies. The conclusion of this study confirms that the Green Literacy program, supported by an authentic evaluation system and effective supervision, is able to internalize religious-ecological values ​​in children in a sustainable manner, thus shaping their profiles as responsible stewards of the earth.